Rancangan Kawasan Khas Janda Baik, Pahang - Asmawi, M. Zainora (2019)
The preparation of Rancangan Kawasan Khas is subject to Town & Country Planning Act 1976, reflecting the importance of Janda Baik as an essential eco tourism spot. The environmental sector is crucial as it should be the basis for tourism based on the availability of stream and serenity of surrounding. However, there are threats to the natural environmental resources. The proposals on environmental conservation will guide Bentong Municipal Council in planning and managing this area. An environmental sensitive area plan is the key product of environmental sector.As a statutory document, this is a policy guidance to the government agencies and other stakeholders.